DETERMINANTS OF ENTERPRISE COLLABORATION ON INNOVATION - Tomasz KIJEK; Anna MATRAS-BOLIBOK; Beata PODSTAWKA (Humanities and Social Sciences)
The paper explores the factors that impact a firm’s propensity to collaborate on innovation activities based on a questionnaire survey conducted with 104 innovation-active enterprises from Lubelskie Voivodeship, covering the years 2017-2019. The factor analysis was applied to categorize collaboration partners into institutional, market, and internal. To explain the enterprise’s propensity to collaborate on innovation, we employed two linear regression models. As determinants of cooperation, we included the absorptive capacity, the firm size, and the scale of activity. The results reveal that absorptive capacity, firm size, and scale of activity significantly enhance collaboration with institutional partners, while firm size has a greater impact on the propensity to collaborate with market partners among microenterprises compared to small enterprises. The findings underscore the role of innovation expenditures and firm-specific characteristics in shaping collaborative innovation behaviors, emphasizing the critical importance of partnerships for fostering innovation in enterprises.